2003
DOI: 10.1073/pnas.0636603100
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of two-stage voltage-dependent activation in K+channels

Abstract: The structure of the voltage sensor and the detailed physical basis of voltage-dependent activation in ion channels have not been determined. We now have identified conserved molecular rearrangements underlying two major voltage-dependent conformational changes during activation of divergent K ؉ channels, ether-à -go-go (eag) and Shaker. Two conserved arginines of the S4 voltage sensor move sequentially into an extracellular gating pocket, where they interact with an acidic residue in S2. In eag, these transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
119
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(133 citation statements)
references
References 31 publications
14
119
0
Order By: Relevance
“…6, which is published as supporting information on the PNAS web site). These salt bridges, which stabilize the open-state structure, represent interactions between amino acid residues that are highly conserved among eukaryotic Kv channels (46)(47)(48). Domain Assembly of Kv1.2 in the Open State.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6, which is published as supporting information on the PNAS web site). These salt bridges, which stabilize the open-state structure, represent interactions between amino acid residues that are highly conserved among eukaryotic Kv channels (46)(47)(48). Domain Assembly of Kv1.2 in the Open State.…”
Section: Resultsmentioning
confidence: 99%
“…3E), so that the intracellular end of S3 moves closer to the S4-S5 linker. Rotation of S4 around its axis and simultaneous rolling of S2 around S4 allow sequential interactions of the four gating-charge-carrying residues in S4 (R294, R297, R300, and R303 in K v 1.2) with the conserved negatively charged residue in S2 (E226 in K v 1.2) as proposed previously (46)(47)(48). Importantly, S4 rotates relative to S3 during the conformational change in contrast to the movement of these two helices as a rigid helical hairpin as predicted in the paddle model of gating (30).…”
Section: Gatingmentioning
confidence: 98%
“…The electrostatic interaction between charged residues helps fold the channel in a proper conformation that efficiently targets the channels to the plasma membrane (31,32). Papazian and colleagues (33,34) also found that divalent ions such as nickel and magnesium can bind to the extracellular ion binding pocket formed by the negatively charged residues at S2 and S3 in ether-à-go-go K ϩ channels, decelerating activation kinetics and/or inhibition of currents. Based on these previous findings, we tested whether the negatively charged residue(s) at the outer portion of IS2 were involved in zinc sensitivity.…”
mentioning
confidence: 99%
“…We have shown that bound ions interact with eag-specific acidic residues in transmembrane segments S2 and S3 (Fig. 1A) and have presented evidence that ion binding directly modulates S4 conformational changes (17,19). Interestingly, ion binding slows the kinetics of both ionic and gating currents, but the magnitude of the effect on ionic currents is much greater than on gating currents (16).…”
mentioning
confidence: 99%